Elements Expressing State in the Uzbek Language - Bekchanova Khushbaroy (Zien Journals, 2024)
This article discusses how words expressing state are expressed through various parts of speech in the grammar of the Uzbek language.
Keywords: state category; independent parts of speech; auxiliary words; verbs